17 Ağustos 1999 Marmara depremi sonrası Türk basınının kamuoyu oluşturma sürecine etkileri - Filizer, Mahmut Said (My University, 2002)
During the earthquake disaster which has effected the whole Marmara Region and called as Marmara Earthquake, thousands of people were died, tens of thousands were injured and many buildings were ruined. The wideness and the population density of the region of the earthquake, which was accepted as one of the biggest disaster of the Turkish history, caused a big chaos after the disaster. With many people waiting for the rescue, problems in transportation, energy and communication arising from ruined buildings and roads, we have witnessed a human tragedy in the region of the disaster. The Turkish media has arrived the region immediately and began to announce whole aspects of the disaster to the public. The newspapers and magazins which are our topic have also transmitted the detailed aspects of the disaster via photographs and news. Turkish press showed great efforts to make a guidance to the public via continuing news throughout the weeks aiming to determine the requirement lists, to convey the relief supply to the region, educate the people about the earthquakes, etc... The Turkish press has never let the things people faced after the earthquake, go out of it's agenda and has helped the public opinion to get conscious. News about the transportation of the relief supply, critical news and comments about the Kızılay, legal rights which can be used against the contractors and other responsible units, news about the aid and rescue teams sent by the neighboor country Greece and also the campaign called as Put One More Brick are the examples of this great effort. In this study, it's been objected to explain the public opinion, various factors effecting the public opinion and effects of the mass communication means in the process of forming public opinion, via historical examples. This study includes the information about the Marmara Earthquake and certain subjects mentioned above. It's been concluded that the Turkish press has fulfilled it's mission of informing the public and revealing the truths via news and comments; especially with the help of live tv broadcastings determining the agenda. MAHMUT SAİD FİLİZER 97004-ZETİ
Keywords: Depremler Türkiye; Kamuoyu Türkiye